THE EFFECT OF BI INTEREST RATE AND INFLATION ON THE RETURN OF THE COMPOSITE STOCK PRICE INDEX (IHSG) AT THE INDONESIA STOCK EXCHANGE (IDX): A VECTOR ERROR CORRECTION MODEL (VECM) APPROACH - Andrian Rinaldi Manik; Dimas Pranaditya Lubis; Mangasi Sinurat; Willy Cahyadi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the influence of the BI Rate and inflation on the return of the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange in the post-pandemic period and the monetary policy normalization period of 2017–2024. The analytical method used is the Vector Error Correction Model (VECM) equipped with Granger causality tests, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD) using 96 monthly data observations processed with EViews 12. The results show that the BI Rate and inflation do not significantly affect the JCI return in either the short or long term, although the results of the Johansen cointegration test indicate a long-term equilibrium relationship between the variables. The results of the Granger causality test also do not find a direct causal relationship between the two macroeconomic variables and the JCI return. The IRF and FEVD analysis strengthen this finding, where the JCI return response to BI Rate and inflation shocks is relatively small, and the variation in the JCI return is largely explained by its own internal factors. This finding indicates that the movement of the JCI return during the research period was more influenced by the internal dynamics of the stock market than domestic macroeconomic factors in the form of the BI Rate and inflation.